Driven by demand : how energy gets its power - Jia, Jimmy Yi-Jie, 1980-; Crabtree, Jason (Cambridge : Cambridge University Press, 2014)
Energy plays a central role in shaping our society and infrastructure, making it increasingly important for today's leaders to understand the impact of energy decisions. Discussions about energy often neglect important historical lessons about previous energy transformations and provide inadequate consideration of context - Driven by Demand takes a fresh approach by exploring the emergence of energy systems, outcomes and priorities. It outlines select historical and current events, challenges, and developing energy trends using a range of case studies. Readers will gain foundational knowledge about energy flows and end-uses, helping them to become more conversant about energy outcomes and priorities. This accessible book paves the way for broader discussions about societal resilience, privacy, and security concerns associated with the move towards 'smart' infrastructure. This is a must-read for business executives, policymakers and students working in energy policy, energy management and sustainable business.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Power resources; Electric power production